Hubungan Pengetahuan Dengan Sikap Ibu Pada Penanganan Pertama Demam Pada Anak Usia 0-59 Bulan Di Wilayah Kerja Puskesmas Rawat Inap Cempaka Banjarbaru Tahun 2017 - Isti Qomah; Kholimatusadiya Kholimatusadiya (HB PRESS, 2019)
Fever is a condition where there is an increase in temperature up to 38Â°C or more. Whereas when the body temperature of more than 40Â°C is called high fever. Fever can affect anyone, children to adulthood. Fever provides an uncomfortable body feeling effect, so very often infants affected by their fever are usually fussy. The first handling of fever in children can be pharmacological therapy and non- pharmacological therapy. The research design used is analytic survey with Cross section approach, with population of 58 respondents. Sampling technique with Accidental Sampling, 32 respondents. The analysis technique using Chi-square test. Based on the results of the study of 32 respondents obtained less knowledge of 13 people (40.6%), who have a negative attitude 17 people (53.1%). Chi-square test result showed that there was a correlation between knowledge with mother attitude on first handling of fever with value Ï (0,000) <Î± (0,05). The results of this study are expected to be an input for health workers in following up health services on the first handling of fever in children.